Exploring the Consequences of the Absence of English Teachers on Students’ English Learning in Rural Schools: A Case Study at Senior High School - Imas Siti Nurjanah; Eva Devi Sofyawati (Universitas Islam Negeri Palopo, 2025)
This study examines the impact of the lack of competent English teachers on student learning in rural schools, focusing on a case study of Nurul Hasan Plus High School. The shortage of English teachers in the 3T (remote, frontier, and outermost) areas has been shown to hamper academic development and reduce student motivation. Through an exploratory qualitative case study approach involving interviews, observations, and documentation, data were collected from 1 principal, 1 substitute teachers, and 4 students. The findings show that schools must rely on substitute teachers from other fields, resulting in inconsistent learning and declining quality. Students feel bored, lack enthusiasm, and experience difficulties in mastering basic skills such as reading, writing, and speaking. Efforts such as self-study using digital media or simple assignments cannot replace the role of professional teachers, while institutional solutions such as the placement of non-specialist teachers are only temporary. This condition widens the educational gap between rural and urban areas. This condition widens the educational gap between rural and urban areas. The study highlights how teacher shortages directly disrupt English learning processes in rural settings and underscores the need for systemic measures to ensure equitable access to qualified English teachers.